Pengaruh Sistem Informasi Akuntansi dan Pengendalian Internal Terhadap Kinerja pada Perusahaan PT Semen Indonesia Distributor - Hayu Rokhma Ningsih; Suwandi Suwandi (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
In a business, efforts must always be made to increase productivity by improving the company's performance conditions. A company is an organization founded by a group of people or businesses to meet human needs. Every company, whether trade or industry, always has a way to make a profit by making sales either on credit or in cash. PT Semen Indonesia Distributor is the place for this research. The approach used in this research is descriptive analysis with data testing applying the SmartPLS 4.0 test. With results where H1 is rejected and H2 is accepted.